Pamięć lat 1912 i 2012: artystyczny plon dwóch Skargowskich rocznic (sztuki plastyczne) - Ożóg, Kazimierz S. (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The text deals with the fragmentary issue of Piotr Skarga’s iconography which is the artistic legacy of the anniversaries celebrated in 1912 and 2012. The remembrance of this Jesuit’s death one hundred years ago stirred up many emotions. It was visible in, for instance, mass manifestations, books, theatre performances or the creations of fine arts. In the reality of the beginnings of the 20th century, what was important was the impact of the image created by Jan Matejko as well as its ideological, virtually mystical, background. This jubilee, celebrated one hundred years ago, has left numerous traces in the arts, some of which have not been retained to this day. The medal by Witold Bieliński; the bust sculptured by Władysław Mazur and Jan Tombiński; or the exquisite bas-relief by Luna Drexler on the Lvov Latin Cathedral were characteristic of those times. However, the level of those works is contrasted with the quality and number of creations dedicated to Skarga during the last anniversary. Both the postage stamp issued by the Polish Postal Service as well as the monument unveiled at the Warsaw Catholic School are not really original. In 2012, Skarga was mentioned most frequently on the Internet, in the forms of memes, which were often obscene and inappropriate.